Dental anxiety and oral health-related quality of life before and after non-surgical periodontal treatment - Piedra Hernández, Lucía (2023)
Objectives: To (1) investigate dental anxiety (DA) and oral health-related quality of life (OHRQOL) before and after nonsurgical periodontal treatment (NSPT) and (2) determine correlations between these patient-reported measures. Materials and methods: Demographics, smoking habits, dental pain, Modified Corah’s Dental Anxiety Scale (MDAS), and Oral Health Impact Profile (OHIP-14) were assessed in eighty-two participants. Results Mean age was 48.3 years ± 11.5. At baseline, 8.5% reported being active smokers. Of non-smokers, 11% reported being an ex-smoker. After NSPT, 11.0% reported smoking. Patients’ maximal pain in the last month decreased after therapy. Before treatment, participants reported higher DA. Extreme DA was observed in 8.5% of participants before therapy. Afterwards, 2.4% of participants reported extreme DA. Fear of having a foreign object in the mouth decreased after NSPT. All OHIP-14 scores, except functional limitation, improved post-treatment. Higher DA was associated with worse OHRQoL before treatment. After treatment, total MDAS score was associated with OHIP-14 global score, physical pain, psychological disability, and social disability. Worse MDAS sub-scores were associated with a higher OHIP-14 global score. Individuals with “normal/slight anxiety” had a significant improvement in OHRQoL, whereas people in the “moderate and extreme anxiety” group did not report a significant improvement. Patients diagnosed with generalized periodontitis (GP) stage III grade B and GP stage IV grade B reported less anxiety after NSPT. Conclusions: Associations of MDAS subcategories with OHIP-14 domain scores were found before and after therapy. DA decreases and OHRQoL enhances after NSPT in patients with “normal/slight” anxiety to dental treatment. Dental practitioners should plan strategies to cope with anxiety to dental treatment and prevent decreases in OHRQoL.